2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6347319
|View full text |Cite
|
Sign up to set email alerts
|

Impact of physical telerehabilitation on functional outcomes in seniors with mobility limitations

Abstract: The goal of this project was to objectively assess potential impact of home-based physical telerehabilitation program on functional outcomes in seniors with mobility limitations. Nine consecutive seniors with mobility limitations were enrolled into a 12-week physical telerehabilitation program. At the end of the program, the mean time that patients took to walk 25 feet decreased from 13.5 to 10.6 seconds, and the mean distance that patients walked in 6 minutes improved from 722.4 to 805.7 feet. The Berg Balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 13 publications
2
11
0
1
Order By: Relevance
“…Our previous studies demonstrated significant potential of telemedicine approaches in supporting home-based exercise in PwMS however they were focused mostly on balance and gait correction and didn't include patients with significant mobility impairments [24][25]. In this study, we introduced a telerehabilitation system supporting comprehensive tailored exercise program that includes flexibility, strengthening and aerobic component.…”
Section: Discussionmentioning
confidence: 95%
“…Our previous studies demonstrated significant potential of telemedicine approaches in supporting home-based exercise in PwMS however they were focused mostly on balance and gait correction and didn't include patients with significant mobility impairments [24][25]. In this study, we introduced a telerehabilitation system supporting comprehensive tailored exercise program that includes flexibility, strengthening and aerobic component.…”
Section: Discussionmentioning
confidence: 95%
“…The success of rehabilitation using VR has been demonstrated 10 , 11 , 12 , 13 , 14 , 15 ) . The accomplishments of a VR-based telerehabilitation system have also been reported 16 , 17 , 18 ) . Nevertheless previous studies of telerehabilitation systems have focused on individual movements, such as finger motion, upper limb motion, walking, and balancing, and no device yet produced can train upper and lower limbs and balancing comprehensively.…”
Section: Introductionmentioning
confidence: 85%
“… 3 5 More recently, a few randomized studies demonstrated that motor rehabilitation treatments delivered via TR achieved similar results as standard rehabilitation care in poststroke patients. 6 8 Meanwhile, high levels of satisfaction with all aspects of TR of brain injuries have been reported. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%